2022
DOI: 10.19173/irrodl.v23i2.5774
|View full text |Cite
|
Sign up to set email alerts
|

Design and Validation of the Virtual Classroom Management Questionnaire A Case Study: Iran

Abstract: Effective classroom management methods are well known, but effective ways of managing classes of beginner teachers remain elusive. Classroom management refers to the wide range of skills and techniques that teachers use to ensure that classes are conducted without destructive student behavior. The present study is applied nonexperimental research. The purpose of this study was to design a tool to measure the effective management of the virtual classroom from the perspective of professors and students in e-lear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…For the latter, it is advisable to concentrate on in-service professional development for teachers. This recommendation is consistent with Wilkinson et al's (2020) and Keshavarz et al's (2022) argument that effective inservice professional development is critical for teachers, and that professional development in online classroom management is essential to prepare teachers for teaching in a digital environment. Amirkhani (2022) and Barrot and Fernando (2023) all found that teachers have a key role in building rapport and creating a positive, safe, and friendly atmosphere within online classes.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…For the latter, it is advisable to concentrate on in-service professional development for teachers. This recommendation is consistent with Wilkinson et al's (2020) and Keshavarz et al's (2022) argument that effective inservice professional development is critical for teachers, and that professional development in online classroom management is essential to prepare teachers for teaching in a digital environment. Amirkhani (2022) and Barrot and Fernando (2023) all found that teachers have a key role in building rapport and creating a positive, safe, and friendly atmosphere within online classes.…”
Section: Discussionsupporting
confidence: 76%
“…The primary objective of education is to empower students to recognise their own worth, establish personal life ideals, and acquire the essential knowledge and skills necessary to pursue their dreams. The classroom serves as the main platform for achieving these goals, and teachers play a pivotal role as the primary managers in this educational process (Keshavarz et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Online learning refers to teaching and learning processes that are provided through the Internet. It includes a wide range of applications to access educational materials, as well as to facilitate teacher-student interaction (Keshavarz, Mirmoghtadaie, & Nayyeri, 2022). In recent years, e-learning systems have been increasingly influencing both classroom and campus-based teaching, but more primarily, such systems are leading to new models or designs for teaching and learning (Bates, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Online learning refers to teaching and learning processes that are provided through the Internet. It includes a wide range of applications to access educational materials, as well as to facilitate teacher-student interaction (Keshavarz, Mirmoghtadaie, & Nayyeri, 2022). A report by Allen and Seamen in 2013 stated that about 6.7 million students took virtual courses in 2011, denoting an increase of about 570,000 students compared to 2010 (Allen & Seaman, 2013).Virtual education is also very common in the field of health sciences (Kohan et al, 2021).…”
Section: Introductionmentioning
confidence: 99%